Psychometric evaluation of the abbreviated Hungarian Faking Orgasm Scale for Women - Csányi, Edit; Basler, Julia; Bereczkei, Tamás; Meskó, Norbert (Frontiers in Psychology, 2024)
Introduction The Faking Orgasm Scale for Women (FOS) was developed to explore the motivations behind women’s self-reported instances of faking orgasm during oral sex and sexual intercourse. In a recent study, a Hungarian version of the FOS was developed, confirming the same factor structure as the original American version, consisting of four factors across two subscales. Methods The current study aimed to develop and validate a brief Hungarian FOS. Factor analysis was conducted with data from 2220 women (mean age = 24.4, SD = 7.48 years). The Item Response Theory (IRT) analysis indicated that retaining four-four scales, each comprising of three items was the optimal solution for the revised shorter version. Validation involved 768 women (mean age = 22.6, SD = 4.54 years) completing a questionnaire package, including the Hungarian Short Form of Reasons for Having Sex Questionnaire (YSEX?-HSF) and Women’s Sexual Working Models Scale (WSWMS). Results The results suggest that the Hungarian 24-item FOS, with its four scales within each of the two sub-scales, provides a reliable and valid measurement of motives for faking orgasm in women. The different reasons behind faking orgasm are associated with different sexual working patterns and sexual motivations. Furthermore, women who reported faking orgasms reported significantly higher levels of sexual distancing and perceived lower care from their partners compared to women who reported not faking orgasms. Women who reported faking orgasm were also more likely to engage in sexual activities to attain personal goals and cope with emotional stress. Discussion The FOS-24 offers both practitioners and researchers a concise and useful instrument for the assessment of faking orgasms.